O aumento da seletividade cox-2 influencia na modulação do edema de pata de rato induzido por carragenina? - Cavalcante, Daniel de Sá (2007)
The anti-inflammatories might present several efects about de therapeutical efficacy being some powerful antiinflammatories, but others act as excellent analgesics. In this study were observed and compared the anti-edematogenic efects of selective COX-2 non-steroidal antiinflammatories, lumiracoxib 5mg/Kg, 30mg/Kg, 100mg/Kg, relatively selected, nimesulide 25mg/Kg, meloxicam 30mg/Kg, non selective COX, diclofenac 20mg/Kg, yet of the glucocorticoids dexamethasone (3mg/Kg) and hydrocortisone (4mg/Kg), on the classic model of the edema on rat paw induced by carrageenan. Each group of four animals got one hour before the subcutaneous injection (sc) of the inflamatory estimulation the dosage of each drug to be tested, being that the control group received saline solution 0.9%. After one hour of the management of those dosages, 0.1% to 1% of carrageenan was injected in the right paw of each animal. The volume of the edema paw was checked four times in between one hour breaks, in a digital pletismograph (Ugo Basile ®).The antiedematogenic effect of each tested drug was determined by the comparission of the results with the control group through the ANOVA test. Dexamethasone (3mg/Kg) and Diclofenac (20mg/Kg) were the drugs with best performance with significative reduction rate of the edema, on the third hour, in 94.20% and 84.43% respectively. But the lumiracoxib on the three concentrations used, 5mg/Kg, 30mg/Kg, 100mg/Kg got significative effect on the reduction of the edema with 47,49%, 61,21%, 47,76% respectively on the third hour. Meloxicam, nimesulide and hydrocortisone also demonstrated eficiency with rates of 42,48%, 62,27% and 58,84% respectively. The current study demonstrated that dexamethasone (3mg/Kg) and diclofenac (20mg/Kg) presented potencial antiedematogenic action and that more COX-2 selective drugs didn’t show eficacy comparable to diclofenac